Standarisasi Dan Strategi Membangun Usaha Olahan Kemasan Berkualitas Di Desa Mundusewu Kecamatan Bareng - Lailatus Sa’adah; Akhmad Taqiyuddin Taqiyuddin; Ulfatun Hasanah; Muhammad Fanani (Asosiasi Dosen Akuntansi Indonesia, 2021)
Revolution 4.0 changes the mindset millennial generation in developing science and discovering several discoveries in the field of technology. Millennial generations who are sensitive to technological developments can master and implement existing technological advances to change the consumptive civilization from offline to online. The internet has a very important role in the Covid-19 era with high competitiveness that can produce innovations in building or developing products and businesses that are managed by students as millennials. With this opportunity, it makes it easier for students to promote various types of products as a source of income, and if managed further they can be used as a source of funding for lectures. The problems experienced by students in entrepreneurship are the difficulty of promoting goods and the lack of innovating a product that is more value-added and the lack of capital for the next business development. Therefore, the Ramadhan bazaar activity program organized by SITE Bima aims to foster and develop an entrepreneurial spirit among students so that they can increase the potential, creativity, innovation in students, and become a forum or business community that can be developed into start-ups. digital business. The method applied in this activity is the preparation of activities, implementation of activities, monitoring, and reporting. After carrying out this activity students can survive by doing entrepreneurship independently in the Covid-19 era and creating new product innovations.